Susceptibility of helminth species from horses against different chemical compounds in Brazil - Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Gomes, Lucas Vinicius Costa [UNESP]; Lopes, Welber Daniel Zanetti [UNESP]; Teixeira, Weslen Fabrício Pires [UNESP]; Maciel, Willian Giquelin [UNESP]; Buzzulini, Carolina [UNESP]; Bichuette, Murilo Abud [UNESP]; Campos, Gabriel Pimentel [UNESP]; Soares, Vando Edésio [UNESP]; Bergamasco, Paula Luzia Formigoni [UNESP]; Oliveira, Gilson Pereira de [UNESP]; et al. (Elsevier B. V., 2015)
By means of parasitological necropsies, the present study aimed to evaluate, in six experiments, the degree of susceptibility or resistance of different helminth species which naturally infect horses to ivermectin 0.2mg/kg, abamectin 0.2mg/kg, moxidectin 0.4mg/kg, trichlorfon 35mg/kg, ivermectin 0.2mg/kg+praziquantel 2.5mg/kg, abamectin 0.2mg/kg+praziquantel 2.5mg/kg and ivermectin 0.2mg/kg+6.6 mg/kg pyrantel. At experimental day zero, the horses were allocated to treatment groups based on average counts of strongylid eggs per gram of feces (EPG) obtained on days -3, -2 and -1. Oxyuris sp. infections were confirmed as positive or negative. All the animals in the six experiments were naturally infected by this helminth species. Each group (control or treated) consisted of six animals. All the assessed Habronema muscae populations analyzed were susceptible to ivermectin, abamectin and moxidectin. Of the six Trichostrongylus axei populations, four were susceptible to ivermectin, abamectin, moxidectin, trichlorfon and ivermectin+praziquantel, and two were resistant to abamectin+praziquantel and ivermectin+pyrantel. Both Strongyloides westeri populations analyzed were susceptible to ivermectin, abamectin, moxidectin and abamectin+praziquantel. For O. equi, resistance was found in four different populations treated with ivermectin, abamectin, moxidectin, trichlorfon and ivermectin+praziquantel. Only combinations of abamectin+praziquantel and ivermectin+pyrantel were effective against this parasite species. All the large strongyles diagnosed in the present study (Strongyus edentatus, Strongyus vulgaris and Triodontophorus serratus) were susceptible to all the chemicals tested, with the exception of trichlorfon. Of the Cyathostominae populations, one was diagnosed as resistant to ivermectin and another to trichlorfon. The remaining populations from this nematode group were considered to be sensitive to ivermectin, abamectin, moxidectin, ivermectin+praziquantel, abamectin+praziquantel and ivermectin+pyrantel. New studies should be performed in different regions to evaluate the efficacy of trichlorfon in others field populations of helminthes.
Keywords: Anthelmintic resistance; Drugs; Efficacy; Horses